A CRITICAL ANALYSIS OF MARGARET ATWOOD’S ORYX AND CRAKE AS “USTOPIA” - James, Sonia; James, Siby; James, Sophia (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article is an attempt to analyse human greed for perfection in the light of Margaret Atwood’s novel Oryx and Crake. Man makes use of his scientific intellect to create creatures to suit his selfish interests through genetic engineering. The poor and powerless are ignored and are even specimens for the clinical trials of the rich. This pursuit leads ultimately to the ruin of human race and civilization.